The Teacher Strategies in Enhancing Fluent Reading Skills of First Grade Students at SD Negeri 03 Binuang Kampung Dalam - Suvina Mardhatillah; Gusnita Efrina; Nofriza Efendi; Stavinibelia Stavinibelia (The Future of Education Journal, 2025)
Reading fluency is a fundamental skill that first-grade students must acquire as a foundation for understanding various subjects. However, in practice, many students are still unable to read fluently, with some even unfamiliar with basic letters. This condition demands the active role of teachers in applying appropriate and effective learning strategies. This study aims to describe the teacher’s strategies in improving reading fluency among first-grade students at SD Negeri 03 Binuang Kampung Dalam. The research employed a descriptive qualitative approach with data collected through observation, in-depth interviews, and documentation. The key informant in this study was the first-grade teacher, Mrs. Triyana Yetra, S.Pd., M.Pd. The findings show that the teacher applied adaptive, comprehensive, and engaging strategies. These included grouping students based on their initial reading abilities, providing age-appropriate and interesting reading materials, using letter cards in educational games, and implementing a gradual learning process starting from storytelling by the teacher to shared reading activities. The teacher also integrated inductive, deductive, mixed, and regressive strategies according to the classroom dynamics. Additionally, involving parents in supporting students' learning at home contributed significantly to their reading progress. These strategies proved effective in enhancing students' focus, motivation, and self-confidence in reading.